Pilot Study of Cartilage Repair in the Knee Joint with Multiply Incised Chondral Allograft. (April 2015) - Bardos, Tamas; Vancsodi, Jozsef; Farkas, Boglarka; Fazekas, Adam; Nagy, Szilvia Anett; Bogner, Peter; Vermes, Csaba; Than, Peter
Background: Focal cartilage lesions in the knee joint have limited capacity to heal. Current animal experiments show that incisions of the deep zone of a cartilage allograft allow acceptable integration for the graft. Questions/Purposes: We performed this clinical study to determine (1) if the multiply incised cartilage graft is surgically applicable for focal cartilage lesions, (2) whether this allograft has a potential to integrate to the repair site, and (3) if patients show clinical improvement. Patients and Methods: Seven patients with 8 chondral lesions were enrolled into the study. Symptomatic lesions between 2 and 8 cm 2 were accepted. Additional injuries were allowed but were addressed simultaneously. Grafts were tailored to match and the deep zone of the cartilage was multiply incised to augment the basal integration before securing in place. Rigorous postoperative physiotherapy followed. At 12 and 24 months the patients' satisfaction were measured and serial magnetic resonance imaging (MRI) was performed in 6 patients. Results: Following the implantations no adverse reaction occurred. MRI evaluation postoperatively showed the graft in place in 5 out of 6 patients. In 1 patient, MRI suggested partial delamination at 1 year and graft degeneration at 2 years. Short Form–36 health survey and the Lysholm knee score demonstrated a significant improvement in the first year; however, by 2 years there was a noticeable drop in the scores. Conclusions . Multiply incised pure chondral allograft used for cartilage repair appears to be a relatively safe method. Further studies are necessary to assess its potential in cartilage repair before its clinical use.